Klebsiella Phage KP34 RNA Polymerase and Its Use in RNA Synthesis - Lu, Xueling; Wu, Hui; Xia, Heng; Huang, Fengtao; Yan, Yan; Yu, Bingbing; Cheng, Rui; Drulis-Kawa, Zuzanna; Zhu, Bin (Frontiers in Microbiology, 2019)
We have characterized the single subunit RNA polymerase from Klebsiella phage KP34. The enzyme is unique among known bacteriophage RNA polymerases in that it recognizes two unrelated promoter sequences, which provided clues for the evolution of phage single-subunit RNA polymerases. As the first representative enzyme from the ‘phiKMV-like viruses’ cluster, its use in run-off RNA synthesis was investigated. RNA-Seq analysis revealed that the KP34 RNA polymerase does not possess the undesired self-templated RNA terminus extension known for T7 RNA polymerase and is suitable to synthesize RNAs with structured 3’ termini such as sgRNAs. A KP34 RNA polymerase Y603F mutant is engineered to incorporate deoxy- and 2’-fluoro-ribonucleotides into RNA.